Experimental Investigation of Two-Way Concrete Slabs Reinforced by Perforated Steel Plates Under Concentrated Load - AL-ZAHID, Ali Adnan; ALWASH, Nameer A. (Engineering Transactions, 2022)
This research experimentally investigates the effect of using the perforated steel plate instead of steel bars as a reinforcing system in two-way concrete slabs. The study consists of casting four slabs using self-compacting concrete. Three slabs are reinforced by a perforated steel plate and one slab is reinforced by traditional bar reinforcement. The amount of steel in both types of reinforcement is equal. The slabs are tested under a monotonic concentrated load at their middle point. The results show a significant enhancement in behavior. The ultimate load increased about 43% to 76%, depending on the size of the openings. Moreover, the final crack width in all slabs reinforced by a perforated steel plate was smaller than in the slab reinforced by a traditional steel bar. The results of this study may be used in future research to introduce a method that will lead to an improvement in the overall behavior of two-way concrete slabs.